Freeze-thaw crack determination in cementitious materials using 3D X-ray computed tomography and acoustic emission. (May 2018) - Shields, Yasmina; Garboczi, Edward; Weiss, Jason; Farnam, Yaghoob
Abstract: As concrete freezes and thaws cracks may develop. These cracks can provide a path for water and ionic species to penetrate the concrete. This may reduce the service-life of the concrete element. In this study, X-ray computed tomography (CT) was used as a non-destructive technique to characterize the microstructure of mortar samples that were exposed to different levels of freeze-thaw damage by varying degree of saturation in the samples (75, 90, 95, and 100% degrees of saturation). Acoustic emission (AE) experiments were performed during freezing and thawing to investigate sample cracking behavior. The volume of cracks present within the mortar samples after freezing and thawing were determined using X-ray CT and compared to passive acoustic emission data. The location/source of cracks was also determined using X-ray CT. The crack sources (i.e., void, aggregate, interfacial transition zone, or paste) were determined using X-ray CT and were related to AE activities during cracking. Crack volumes were found to increase with increased levels of saturation, and visual observations of cracking were found to correlate with AE signatures of various crack sources.